GAMBARAN POLA MAKAN DAN STATUS GIZI PADA PEKERJA BURUH PANEN (PENDODOS KELAPA SAWIT) PTPN IV UNIT AJAMU KECAMATAN PANAI HULU KABUPATEN LABUHANBATU TAHUN 2017 - Khairani Ritonga; Ernawati Nasution; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Nutrition status is the state of a person or group of people caused by diatery habits, absorption and use of nutrients. The purpose of this research is to know the description of eating pattern and nutritional status of Harvest Workers PT. Perkebunan Nusantara IV Subdistrict Panai Hulu District Labuhanbatu Year 2017. The type of research is descriptive. Sampling was done by stratified random sampling with total sample of 67 workers. Data collection is done directly to harvest workers using structured questionnaires. Types of food, frequency of food, and amount of energy and nutrient intake were seen using 24-hour recall form and food frequency. The results showed that the diet of workers based on the type of food, 100% consume rice as staple food, 52.2% consume eggs, 99.1% consume kale, 53.73% consume oranges, 61.19% consume tea 68.68%. While eating based on the frequency of eating, most eating staple food with a frequency of 2-3 times / day, side dishes with frequency 4-6 times a week, vegetables with frequency 4-6 times a week, fruit with 1-3 times the frequency / Sunday. In energy consumption 67.12% of workers' needs. Similarly, carbohydrate consumption of 68.7% is sufficient. Protein consumption 58.2% is sufficient. Fat consumption 52,2% is sufficient Needs Nutritional status of workers based on body mass index found at 28.4% of nutritional status is less, 68.6% normal, and 3% with more nutritional status. Suggestions in this research for the company to conduct examination of workers harvest workers in the implementation of breakfast. Keywords : Dietary habits, Nutrition status, Harvest workers